Clinical features, diagnosis and thoracoscopic surgical treatment of thymic cysts - Wang, Xun; Chen, Kezhong; Li, Xiao; Li, Yun; Yang, Fan; Li, Jianfeng; Jiang, Guanchao; Liu, Jun; Wang, Jun (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Background: Thymic cysts are rare benign developmental anomalies and there is no consensus management for thymic cysts. The aim of this study was to disclose the efficacy of perioperative diagnosis for thymic cysts by chest computerized tomography (CT) and to elucidate the surgical procedure by video-assisted thoracic surgery (VATS) in the management of thymic cysts. Methods: We retrospectively reviewed 108 consecutive thymic cyst patients who underwent VATS at our institution between April 2001 and August 2015. All patients received chest CT preoperatively and underwent VATS treatment. Clinical characteristics, imaging features and surgical exploration were taken into consideration to determine the surgical extent. Results: Multivariate logistic regression analysis showed that a diameter ≤3 cm [risk ratio (RR)=4.525; 95% confidence interval (CI), 1.027–20.000; P=0.046] and an unenhanced CT value >20 Hounsfield unit (Hu) (RR=7.043; 95% CI, 1.750–28.345; P=0.006) were independent factors of incorrect diagnosis of chest CT. Three different surgical procedures were performed, which included thymectomy (n=49), cyst resection and partial thymectomy (n=46), and extended thymectomy (n=13). No serious postoperative complications were observed. The median follow-up-time was 60.6 months (range, 12.0–168.0 months) with no late complications or recurrences. Conclusions: A diameter ≤3 cm and an unenhanced CT value >20 Hu were independent factors of incorrect diagnosis of chest CT. VATS is a reliable approach for the surgical resection of thymic cysts. We think that local resection is adequate for simple thymic cysts. However, thymectomy is necessary when there is suspicion of a thymoma or multilocular thymic cyst, and radical thymectomy is advisable for patients with autoimmune diseases.